A Radiobrominated Tyrosine Kinase Inhibitor for EGFR with L858R/T790M Mutations in Lung Carcinoma - Muammar Fawwaz; Kenji Mishiro; Ryuichi Nishii; Akira Makino; Yasushi Kiyono; Kazuhiro Shiba; Seigo Kinuya; Kazuma Ogawa (MDPI AG, 2021)
Activating double mutations L858R/T790M in the epidermal growth factor receptor (EGFR) region are often observed as the cause of resistance to tyrosine kinase inhibitors (TKIs). Third-generation EGFR-TKIs, such as osimertinib and rociletinib (CO-1686), was developed to target such resistance mutations. The detection of activating L858R/T790M mutations is necessary to select sensitive patients for therapy. Hence, we aimed to develop novel radiobromine-labeled CO-1686 as a positron emission tomography (PET) imaging probe for detecting EGFR L858R/T790M mutations. Nonradioactive brominated-CO1686 (BrCO1686) was synthesized by the condensation of N-(3-[{2-chloro-5-(trifluoromethyl)pyrimidin-4-yl}amino]-5-bromophenyl) acrylamide with the corresponding substituted 1-(4-[4-amino-3-methoxyphenyl]piperazine-1-yl)ethan-1-one. The radiobrominated [77Br]BrCO1686 was prepared through bromodestannylation of the corresponding tributylstannylated precursor with [77Br]bromide and N-chlorosuccinimide. Although we aimed to provide a novel PET imaging probe, 77Br was used as an alternative radionuclide for 76Br. We fundamentally evaluated the potency of [77Br]BrCO1686 as a molecular probe for detecting EGFR L858R/T790M using human non-small-cell lung cancer (NSCLC) cell lines: H1975 (EGFR L858R/T790M), H3255 (EGFR L858R), and H441 (wild-type EGFR). The BrCO1686 showed high cytotoxicity toward H1975 (IC50 0.18 ± 0.06 µM) comparable to that of CO-1686 (IC50 0.14 ± 0.05 µM). In cell uptake experiments, the level of accumulation of [77Br]BrCO1686 in H1975 was significantly higher than those in H3255 and H441 upon 4 h of incubation. The radioactivity of [77Br]BrCO1686 (136.3% dose/mg protein) was significantly reduced to 56.9% dose/mg protein by the pretreatment with an excess CO-1686. These results indicate that the binding site of the radiotracers should be identical to that of CO-1686. The in vivo accumulation of radioactivity of [77Br]BrCO1686 in H1975 tumor (4.51 ± 0.17) was higher than that in H441 tumor (3.71 ± 0.13) 1 h postinjection. Our results suggested that [77Br]BrCO1686 has specificity toward NSCLC cells with double mutations EGFR L858R/T790M compared to those in EGFR L858R and wild-type EGFR. However, the in vivo accumulation of radioactivity in the targeted tumor needs to be optimized by structural modification.